Environmental conditions for polar low formation and development over the Nordic Seas: study of January cases based on the Arctic System Reanalysis. Issue 1 (1st January 2019) - Radovan, Ana; Crewell, Susanne; Moster Knudsen, Erlend; Rinke, Annette
Abstract: The sparse observational network over the Arctic region makes severe storms such as polar lows (PLs) still hard to predict. To improve their forecasting and detection, it is of great importance to gain better understanding of their formation and development. Therefore, we have analyzed the environment of PLs at their genesis and mature stages using a set of parameters: the difference between sea surface and 500 hPa temperature (or at 2 m height), lapse rate (LR) and relative humidity below 850 hPa (RH), near-surface wind speed and geopotential height anomaly. We evaluate which of these conditions (or which combination) is(are) the most favourable for PL formation and persistence. The analysis was performed on 33 January cases over 12 years (2000–2011) using the Arctic System Reanalysis. The results showed that, for the cases with lower thermal instability during formation stage, LRs throughout the boundary layer were stronger and steeper; therefore, these PLs were fostering convective development. However, for few cases, it was noted that when convection decreased simultaneously with increased thermal stability, RH most of the times was above 90%. It was also noted that the higher amount of RH at lower levels during genesis stage promoted stronger winds at the maturity stage.